APPLICATION OF MULTI-OBJECTIVE EVOLUTIONARY ALGORITHM BASED ON DECOMPOSITION FOR DOUBLE U-SHAPED ASSEMBLY LINE BALANCING - ตันชนะประดิษฐ์ สุชานันท์ (Srinakharinwirot University Engineering Journal, 2018)
This article proposes a mixed-model double U-shaped assembly line. Two individual U-shaped lines are placed adjacently in parallel. The double U-shaped line balancing problem in this research optimizes many objectives simultaneously, i.e. minimum number of workstations, minimum number of stations, minimum work unrelatedness, minimum different workload between and within workstation. This research applies a Multi-Objective Evolutionary Algorithm based on Decomposition (MOEA/D) to find the optimum solution since this approach is found to be effective for many-objective optimization problems. The experiment results show that MOEA/D performs better than MOPSO in terms of convergence and ratio of non-dominated solution. Thus MOEA/D is suitable for solving Double U-shaped line balancing problem with many objectives.